2019
DOI: 10.1039/c9qi00663j
|View full text |Cite
|
Sign up to set email alerts
|

Design of Mo-doped cobalt sulfide hollow nanocages from zeolitic imidazolate frameworks as advanced electrodes for supercapacitors

Abstract: A Mo-doped CoS HNC with enhanced electrochemical performance was designed by using ZIF-67 as a self-sacrificial template through a dissolution–regrowth process in the presence of NaMoO4 with an additional sulfurization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The O−Co 3 S 4 /CP electrode also shows the higher capacitance retention of around 65 % than 43 % of Co 3 S 4 /CP at 10 A g −1 . The electrochemical performance of O−Co 3 S 4 /CP is competitive in comparison with those of other cobalt sulfide electrodes reported in previous literatures (Table S1) [15,33–41] . The electrochemical impedance spectroscopy (EIS) was employed to understand the electrical resistance and charge‐transport behavior of Co 3 S 4 /CP and O−Co 3 S 4 /CP electrodes.…”
Section: Resultsmentioning
confidence: 95%
“…The O−Co 3 S 4 /CP electrode also shows the higher capacitance retention of around 65 % than 43 % of Co 3 S 4 /CP at 10 A g −1 . The electrochemical performance of O−Co 3 S 4 /CP is competitive in comparison with those of other cobalt sulfide electrodes reported in previous literatures (Table S1) [15,33–41] . The electrochemical impedance spectroscopy (EIS) was employed to understand the electrical resistance and charge‐transport behavior of Co 3 S 4 /CP and O−Co 3 S 4 /CP electrodes.…”
Section: Resultsmentioning
confidence: 95%
“…Thirdly, the interconnect nanosheet arrays on NF provide a stable structure and shorten the diffusion path of ions and electrons. Finally, Co element is responsible for providing high capacity and Mo element is responsible for improving the stability of the electrode [31,32].…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Upon comparing the proposed HSC performance with those of previously reported metal-oxide/metal-sulfide HSC structures, it was observed that the energy densities were comparable without any reduction of power density. Notably, the energy density of the HSC is comparable to or superior than those of the CoS//AC cells (5.3 W h kg −1 at 1800 W kg −1 ), 47 59 CoS/graphene//AC HSC (29 W h kg −1 at 800 W kg −1 ), 60 CoS/Co 9 S 8 //AC HSC (46.2 W h kg −1 at 550 W kg −1 ), 61 Mn-doped CoS//AC HSC (27.7 W h kg −1 at 799.9 W kg −1 ), 38 and CoS on S/N-doped graphene foam// graphene foam HSC (33.2 W h kg −1 at 374.7 W kg −1 ). 62 The advantages of the porous structure and the effective pseudocapacitive nature of the defect-enriched Co oxysulfide with C interface infuse higher current sweeps with the electrochemical reduction sites.…”
Section: Coos 2 + Ohmentioning
confidence: 99%